2023
DOI: 10.3389/fmicb.2023.1221724
|View full text |Cite
|
Sign up to set email alerts
|

Further evidences of an emerging stingless bee-yeast symbiosis

Abstract: Symbiotic interactions between microorganisms and social insects have been described as crucial for the maintenance of these multitrophic systems, as observed for the stingless bee Scaptotrigona depilis and the yeast Zygosaccharomyces sp. SDBC30G1. The larvae of S. depilis ingest fungal filaments of Zygosaccharomyces sp. SDBC30G1 to obtain ergosterol, which is the precursor for the biosynthesis of ecdysteroids that modulate insect metamorphosis. In this work, we find a similar insect-microbe interaction in oth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Studies regarding ecological relationships and fungal species composition in substrates related to native bees are still rare. In Brazil, the relationship between fungi and Scaptotrigona depilis has been investigated [28][29][30]. In addition, other studies have reported the presence of different microorganisms associated with other genera of stingless bees [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding ecological relationships and fungal species composition in substrates related to native bees are still rare. In Brazil, the relationship between fungi and Scaptotrigona depilis has been investigated [28][29][30]. In addition, other studies have reported the presence of different microorganisms associated with other genera of stingless bees [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Fall armyworm ( Spodoptera frugiperda ) harbors fungal symbionts such as Fusarium oxysporum and Cladosporium sp ( Watson et al., 2023 ). Like other insects, bees depend on a symbiotic relationship with microbes, ranging from pathogenic to mutually beneficial ( de Paula et al., 2023 ; Rutkowski et al., 2023 ). Common fungal symbionts include yeasts from the taxa of Starmerella , Metschnikowia , Zygosaccharomyces , and Candida , which are found across various tribes and species ( Rutkowski et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…postica , Sc. tubiba , Tetragona clavipes , Melipona quadrifasciata , M. fasciculata , M. bicolor , and Partamona helleri ( de Paula et al., 2023 ). Additionally, Liu et al.…”
Section: Introductionmentioning
confidence: 99%